国际麻醉品管制局 报告 2023 - International Narcotics Control Board (United Nations, 2024)
This annual report prepared by The Board provides a comprehensive account of the global drug situation, analyses trends in drug abuse and drug trafficking and suggests necessary remedial action. Divided into four parts, it covers the following topics: drugs and corruption, functioning of the international drug control system, analysis of the world situation and finally, a set of recommendations to governments, the United Nations and other relevant international and regional organizations.